THE INFLUENCE OF THE EFFECTIVENESS OF PRINCIPAL AND TEACHER SUPERVISION ON EFL STUDENTS' DISCIPLINE - Lestari Budianto; Muhammad Saifuddin Zuhri (IKIP Siliwangi, 2024)
Discipline is the most important thing for the progress of a nation. The role of school principals and school teachers must be able to make breakthroughs in the management of improving discipline. The success of improving discipline in schools is very dependent on the effectiveness of supervision regarding supervision and monitoring of existing human resources. This research aims to describe the effectiveness of supervision by principals and teachers on EFL students’ discipline at SMP GIKKI 1 SURABAYA as well as on improving discipline. This research uses quantitative methods to analyze the relationship between variables. The data obtained were analyzed with the SPSS version 27.00 statistical program using statistical techniques in the form of validity and reliability tests, and variable expressions used in the survey. The results of the research show that the effectiveness of joint supervision by the principal and school teachers has a positive and significant effect on the quality of discipline and education at SMP GIKKI 1 SURABAYA.